Soluble guanylate cyclase stimulators and their potential use: a patent review. (4th March 2021) - Sandner, Peter; Vakalopoulos, Alexandros; Hahn, Michael G.; Stasch, Johannes-Peter; Follmann, Markus
ABSTRACT: Introduction : In 2013, riociguat a potent and specific stimulator of the soluble guanylyl cyclase (sGC) was approved as first in class sGC stimulator which reflected a first culmination of intense research and development efforts starting in the mid 1990ies. In the meantime, it turned out that triggering cGMP production by sGC stimulators could have a broad treatment potential. In consequence, various pharmaceutical companies are still very active in identifying novel chemistry for sGC stimulators. After the first generation of sGC stimulators like riociguat or lificiguat, new compound classes with different physicochemical and kinetic profiles were identified, like the sGC stimulators vericiguat or praliciguat. Area covered : Patent literature on sGC stimulators with a focus on recent compounds of the years 2014–2019 as on claimed use and formulations of these compounds. The information was collected from publicly available data sources only (MedLine, EmBase, Chemical Abstracts, Orbit, Dolphin). Expert Opinion : With the recent advancements reported in the patent literature, sGC stimulators might be differentiated due to tissue selectivity or route of application although exhibiting the same molecular mode of action. The indication space of these compounds is potentially very broad and multiple indications in cardiovascular diseases and beyond are under investigation